High Production of LukMF’ in Staphylococcus aureus Field Strains Is Associated with Clinical Bovine Mastitis - Hoekstra, Jurriaan (Toxins (Basel), 2018)
Staphylococcus aureus, a major cause of bovine mastitis, produces a wide range of immune-evasion molecules. The bi-component leukocidin LukMF’ is a potent killer of bovine neutrophils in vitro. Since the role of LukMF’ in development of bovine mastitis has not been studied in natural infections, we aimed to clarify whether presence of the lukM-lukF’ genes and production levels of LukMF’ are associated with clinical severity of the disease. Staphylococcus aureus was isolated from mastitis milk samples (38 clinical and 17 subclinical cases) from 33 different farms. The lukM-lukF’ genes were present in 96% of the isolates. Remarkably, 22% of the lukM-lukF’-positive S. aureus isolates displayed a 10-fold higher in vitro LukMF’ production than the average of the lower-producing ones. These high producing isolates were cultured significantly more frequently from clinical than subclinical mastitis cases. Also, the detection of LukM protein in milk samples was significantly associated with clinical mastitis and high production in vitro. The high producing LukMF’ strains all belonged to the same genetic lineage, spa-type t543. Analysis of their global toxin gene regulators revealed a point mutation in the Repressor of toxins (rot) gene which results in a non-functional start codon, preventing translation of rot. This mutation was only identified in high LukMF’ producing isolates and not in low LukMF’ producing isolates. Since rot suppresses the expression of various toxins including leukocidins, this mutation is a possible explanation for increased LukMF’ production. Identification of high LukMF’ producing strains is of clinical relevance and can potentially be used as a prognostic marker for severity of mastitis.